Detection of the pulp-froth interface using the ultrasound transit time technique. (1st January 2021) - Richter, T.; Heitkam, S.; Odenbach, S.; Eckert, K.
Graphical abstract: Highlights: Detection of the pulp-froth interface in a lab-scale flotation setup. Ultrasound transducers attached to the bottom of the tank. Simultaneous measurement of the speed of sound of the pulp. Accuracy of the level height measurements equals to 1.5%. Abstract: The vertical position of the pulp-froth interface in a flotation cell is an important parameter in froth flotation processes which needs to be controlled in situ. For this purpose, we introduce the ultrasound transit time technique (UTTT), a non-invasive technique for detecting and measuring the position of this interface. Based on lab-scale experiments, the method is evaluated for a pulp-air and a pulp-froth interface. The technique was found to be well applicable in pulp with up to 21 % particle mass fraction. In a container with 80 mm height the accuracy is found to equal 1 mm .